Perinatal outcomes following an earlier post‐term labour induction policy: a historical cohort study. (18th February 2015) - Hedegaard, M; Lidegaard, Ø; Skovlund, CW; Mørch, LS; Hedegaard, M
<x xml:space="preserve">Abstract</x> Objective To assess the changes in perinatal outcomes in children born from 37 weeks of gestation after implementation of a more proactive labour induction practice from 2009. Design Register‐based cohort study. Setting Denmark, 2000–12. Population Newborns from 37 weeks of gestation. Methods Perinatal outcomes were estimated using a logistic regression analysis with adjustment for gestational age, maternal age, parity, plurality, smoking and body mass index. Main outcome measures Perinatal outcomes. Results A total of 770 926 infants were included. Labour induction from 37 weeks increased from 9.7% in 2000–02 to 22.5% in 2011–12. From 2003–05 to 2011–12, the risk of umbilical cord pH < 7.0 decreased by 23%; odds ratio (OR) 0.77 (95% confidence interval 0.67–0.89), and the adjusted OR of Apgar score < 7 at 5 minutes was unchanged. The risk of admission to neonatal intensive care units increased by 56%; OR 1.56 (1.47–1.66), whereas the risk of neonatal deaths decreased by 44%; OR 0.56 (0.45–0.70). The risk of cerebral palsy was from 2000–02 to 2009–10 reduced by 26%; OR 0.74 (0.60–0.90). The proportion of infants born with fetal weight ≥ 4500 g decreased by one‐third; OR 0.68 (0.65–0.71). However, the risk of shoulder dystocia increased by 32%; OR 1.32 (1.21–1.44), whereas the risk of peripheral nerve injuries was reduced by 43%; OR 0.57 (0.45–0.73). Conclusion The results suggest an overall improvement in perinatal outcomes as a result of a more proactive post‐term labour induction practice.